2016
DOI: 10.1002/clen.201500225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Source Apportionment of Atmospheric Particles Across Multiple Sampling Locations in Faisalabad, Pakistan

Abstract: Atmospheric particles (total suspended particles, TSPs) mass samples (288) were collected by high volume samplers at nine sampling locations in Faisalabad, Pakistan from May 2012 to April 2013. These TSP mass samples were subjected to gravimetric and quantitative chemical analyses for determining trace elements (Pb, Cd, Ni, Zn, Cu, Fe) using atomic absorption spectroscopy and water-soluble cations (Ca 2þ , Mg 2þ , Na þ and K þ , NH 4 þ ) and anions (Cl À , SO 4 2À , and NO 3 À ) by ion chromatography. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 36 publications
(117 reference statements)
2
14
1
Order By: Relevance
“…Over 50 years, air pollution and its impact on human health are a concern for the World Health Organization (WHO). For this reason guideline with the aim to protect public health from the adverse effects of air pollutants has developed [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Over 50 years, air pollution and its impact on human health are a concern for the World Health Organization (WHO). For this reason guideline with the aim to protect public health from the adverse effects of air pollutants has developed [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ions like SO 4 2-, NO 3 -and NH 4 + are strongly correlated, indicating their common origin as secondary particle compounds in the atmosphere (Shen et al, 2007(Shen et al, , 2009Cheung et al, 2011). Noted irregular and inconsistent correlation patterns suggested that these elements possibly originate from several sporadic local sources that are described and applied in a companion paper (Javed et al, 2015).…”
Section: Correlation Among Tsp Chemical Speciesmentioning
confidence: 86%
“…High PM mass concentrations at SL4 (a rural site) were possibly due to combustion of low quality fuel currently being used in two brick kilns located at this sampling location. Low quality coal, wood, used rubber tires and waste oil are mostly used for fuel in these kilns located within the study area (Javed et al, 2015). On the contrary, the lowest PM concentration was recorded at a remote rural site (SL9) because the sorrounding area (up to 15 km 2 ) had no vehicular and industrial activities throughout the sampling period.…”
Section: Aerosol Particulate Matter (Pm) Concentrationsmentioning
confidence: 89%
“…[74,75] The information about ionic profile is not only important for source apportionment studies but also understanding of tropospheric chemistry. For this purpose, Javed et al [45] determined the fraction of water-soluble cations and anions in the particulate samples collected in Faisalabad from May 2012 to , respectively. These concentrations appeared due to the dust re-suspensions at rapid wind speeds.…”
Section: à3mentioning
confidence: 99%
“…[72] PAHs were mainly produced from partial combustion of oil and coal, [49] whereas ions were assumed to originate from coal, biomass, waste burning, and earth crust. [45,52] …”
Section: Sources Of Organic-inorganic Particulate Emissionsmentioning
confidence: 99%